A Case on the HRM Model in One Indian Based Japanese Trading Establishment - Merudi, Deepthi (Prabandhan: Indian Journal of Management, 2016)
Indian-based Japanese companies tend to concentrate more on providing communications rather than creating a structural human resource management system that incorporates all the essential instruments of effective communication. For a notable progress of any company, human relations are crucial. Proper interpersonal relationships and cross- cultural management are necessary in creating a defined organizational structure. Career development and enlisting of the job requirements are some of the elements that dictate the performance of humans. Similarly, a healthy work environment through a structured human resource model and motivation plays an important role in defining the outcome of productivity. The synergy of all these human resource components is essential in organizational operations and effectiveness. This research paper focused on studying such elements of international management of human resources through a case study of India-based Japanese establishments with their human resource models. On the basis of these findings, recommendations for improving the human resource system and practices are suggested.